THEORETICAL FOUNDATIONS OF PROJECT-BASED WORK - Djurayeva Nargiza Abdukarimovna (Web of Journals Publishing, 2025)
Project-based work is a modern approach aimed at active participation of students in the educational process, development of their creative thinking and practical skills. This approach allows students to put their knowledge into practice, and also makes the learning process more interesting and effective. It is necessary to understand the theoretical foundations of project-based work, to understand its importance in the educational process, and to consider the possibilities of its practical application.
Keywords: Project-based learning, theory, group discussions, skills, teaching methods, knowledge, practice.